Male and Female Students’ Perception on the Use of Popular Song to Improve Students’ Vocabulary Mastery - Etika Rachmawati; Rita Apollonia; Imelda Ratna Meila (Yayasan Karinosseff Muda Indonesia, 2020)
This study was aimed to investigate the students’ perception and the teacher’s way to teach popular song to improve students’ vocabulary mastery. The sample of the study was 32 first year students in Vocasional higt school.A qualitative case study was employed, the data were obtained through the observation and questionnaire. Then, the data from the observations were analyzed by transcribing the whole of the activity in classroom and data from questionnaire were presented into percentage. The researcher described the data of the observation qualitatively. In the present study, the researcher proposed three research questions: (1) How does the teacher use popular song to improve students’ vocabulary mastery at English club? (2) What are male students’ perceptions on the use of popular song to improve students’ vocabulary mastery? And (3) What are female students’ perceptions on the use of popular song to improve students’ vocabulary mastery? In responding to the first research question, it was found that the teacher used audio technique such as music in teaching vocabulary. Furthermore, the result of second and third research question found that male and female students agreed that popular song could improve students’ vocabulary mastery, it can be seen from the questionnaire. It showed that students got new vocabularies after listening, learning and reading popular song because it had many new vocabularies and easy to understand. Based on the conclusion, this study suggests that the teachers who teach English, teaching English need various technique, method, and approach that have to apply in teaching learning process in order to give new atmosphere for the students. Using popular song as one of the solution to solve that problem has to be developed by the teachers because there are some activities that could make teaching learning English more fun and enjoyable especially in improving students’ vocabulary mastery because it is rich with vocabularies. Furthermore, the students have to learn deeply about the component of English and learning vocabulary in order to make them mastering English.